Pengaruh Penggunaan Buku Ajar Ilmu Balaghah Berbasis Hadis Qudsi terhadap Peningkatan Pemahaman Ilmu Balaghah Mahasiswa PBA IAIN Sultan Amai Gorontalo - Hj. Bahri, Ratni Bt.; Damhuri, Damhuri (Yayasan Daarul Qimmah Gorontalo, 2023)
The study of ilm al-balaghah (rhetoric) among university students often faces challenges in understanding rhetorical concepts deeply, primarily due to the theoretical nature and lack of contextualization in the teaching materials used. This study aims to analyze the impact of using an ilm al-balaghah textbook based on hadith qudsi on improving students' understanding in the Arabic Language Education (PBA) program at IAIN Sultan Amai Gorontalo. This research employs a quantitative method with a quasi-experimental design. The population consists of PBA students at IAIN Sultan Amai Gorontalo, with the sample selected through purposive sampling. The research instrument consists of a pre-test and post-test measuring students' understanding of ilm al-balaghah before and after using the textbook. Data analysis was conducted using statistical tests to evaluate the differences in students' understanding before and after the intervention. The findings indicate that the use of an ilm al-balaghah textbook based on hadith qudsi significantly contributes to improving students' comprehension. The textbook facilitates a more contextual and practical understanding of ilm al-balaghah concepts. Statistical analysis revealed a significant increase in students' comprehension scores after applying the textbook in the learning process. Therefore, this book is recommended as an alternative teaching material for rhetoric studies in higher education.